Environment and society: Serra de Itabaiana National Park in debate / Ambiente e sociedade: O Parque Nacional Serra de Itabaiana em debate - Claydivan Wesley dos Santos Souza; Marcelo Alário Ennes (Universidade Estadual de Alagoas, 2016)
The aim of this work is to understand how they are established the links between environment and society from an interdisciplinary approach in the Serra de Itabaiana National Park. However, with regard to the environment and society emblem in protected areas we need to consider that environmental conservation is not just an ecological problem, but relates primarily to a social rationality. The work of this study area comprises the Serra de Itabaiana National Park and the community of Good garden, populated Itabaianense. The National Park of Sierra Itabaiana- Parnasi, created on June 15, 2005, located in Sergipe wild in a transition zone between the savanna and the Atlantic Forest, the predominant climate framework is the semiarid region. Distant 45 km from Aracaju, capital of the state of Sergipe, is inserted in the municipalities of Areia Branca, Itabaiana, Itaporanga D`ajuda, Orange and Brito Field. Its area covers 7,966 hectares, 87.25 km perimeter and is administered by the Chico Mendes Institute for Biodiversity Conservation (ICMBio). The community of the town of Bom Jardim, located in the municipality of Itabaiana and the surrounding area Parnasi (or buffer zone is the range of three thousand meters beyond the official limits of UC. In this area human activities are subject to specific rules and restrictions , in order to minimize negative impacts on the unit), it is a complex social context and sharpens the scientific interest because instigates research into the coexistence of community in your expectations, limits and established connections with the said conservation unit. We use the qualitative method to be the most consistent way to understand a social phenomenon and its peculiarities. As procedures, we conducted in-depth interviews with four residents informants in Bom Jardim and ICMbio manager. Environmental changes need to be analyzed within the context in which they operate, for the environment and society are inextricably linked, but may experience misunderstandings due to different conceptions and multiple interests involved.